Abomasal Disorders in Dairy Cows During the Transition Period: Interconnected Risk Factors and Repercussions on Health and Culling Rate - Enzo Freire Santana do Amaral; Gabriela Anteveli; João Pedro Matiello; Barbara Andrade Alves; Guilherme Silva Lemos; Helena Ferreira Lage; Rodrigo Melo Meneses; Tiago Facury Moreira; Elias Jorge Facury Filho (Animals, 2026)
The transition period in dairy cows increases susceptibility to various diseases. Abomasal diseases, particularly abomasal displacement (AD) and abomasal ulcers (AU), are important causes of production losses, early culling, and compromised animal welfare. However, few contemporary reviews have comprehensively synthesized these conditions. This narrative review aims to critically synthesize the main risk factors, integrate the underlying pathophysiological mechanisms, and present recent advances in diagnosis and treatment. Evidence indicates that AD and AU are disorders closely associated with a negative energy balance, hypocalcemia, and systemic inflammation. These factors interact through complex immunometabolic pathways. Inflammatory activation, often triggered by endotoxins or sterile inflammation, increases pro-inflammatory cytokine production, disrupts calcium homeostasis, and gastrointestinal neuromuscular function. Consequently, there is a reduction in ruminal and abomasal motility, decreased dry matter intake, and a greater predisposition to gas accumulation and abomasal displacement, in addition to alterations in the integrity of the abomasal mucosa that favor ulcer formation. Furthermore, concomitant diseases such as subclinical ketosis, metritis, lameness, and subacute ruminal acidosis amplify these processes. Despite advances in diagnosis, clinical overlap with other digestive disorders remains a challenge. Preventive strategies should prioritize nutritional management, modulation of inflammation, and maintenance of metabolic homeostasis. Current evidence suggests that AD and AU may be associated with systemic immunometabolic dysregulation rather than representing entirely isolated disorders. However, further studies are needed to confirm the proposed mechanisms in cattle and to determine their implications for prevention and control strategies.